Calcined Clays for Sustainable Concrete Proceedings of the 2nd International Conference on Calcined Clays for Sustainable Concrete (RILEM Bookseries,, 2018)
This volume focuses on research and practical issues linked to Calcined Clays for Sustainable Concrete. The main topics are geology of clays, hydration and performance of blended system with calcined clays, alkali activated binders, applications in concrete and mortar, durability of concrete under various aggressive conditions, and economic and environmental impacts of the use of calcined clays in cement based materials. This book compiles the different contributions of the 2nd International Conference on Calcined Clays for Sustainable Concrete, which took place in La Habana, December 5th-7th, 2017.The papers update the latest research in their field, carried out since the last conference in 2015. Overall it gives a broad view of research on calcined clays and their application in the field of construction, which will stimulate further research into calcined clays for sustainable concrete.